2011
DOI: 10.2174/092986711795656081
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Catecholamine Reactive Intermediates and Oxidative Stress to the Pathologic Features of Heart Diseases

Abstract: Pathologic heart conditions, particularly heart failure (HF) and ischemia-reperfusion (I/R) injury, are characterized by sustained elevation of plasma and interstitial catecholamine levels, as well as by the generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS). Despite the continuous and extensive research on catecholamines since the early years of the XX(th) century, the mechanisms underlying catecholamine-induced cardiotoxicity are still not fully elucidated. The role of catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 571 publications
(1,144 reference statements)
0
101
0
1
Order By: Relevance
“…The pathomechanism for this clinical observation remains uncertain; however, there are several hypotheses to explain the hypotensive shock after exposure to high levels of catecholamines. Desensitization of adrenoreceptors, constricted circulatory volume, vasodilatation by abrupt withdrawal of norepinephrine and catecholamine-induced cardiotoxic effects leading to a left ventricular failure have been discussed as possible mechanisms (8,16,17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The pathomechanism for this clinical observation remains uncertain; however, there are several hypotheses to explain the hypotensive shock after exposure to high levels of catecholamines. Desensitization of adrenoreceptors, constricted circulatory volume, vasodilatation by abrupt withdrawal of norepinephrine and catecholamine-induced cardiotoxic effects leading to a left ventricular failure have been discussed as possible mechanisms (8,16,17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…As stated, the fastest cyclization rate occurs in ADR (Bindoli et al, 1992); however, GSH adducts and quinoproteins of ADR have been found in cells, thus showing that ADR quinone can also undergo attack from cellular nucleophiles (Costa et al, 2007, Costa et al, 2009a, Costa et al, 2009c. These changes can ultimately cause cellular injury (Costa et al, 2011).…”
Section: Another Pathway To Degrade Catecholaminesmentioning
confidence: 92%
“…Of relevance, the oxidative deamination of catecholamines by MAO leads to another relevant product, hydrogen peroxide (H 2 O 2 ) which subsequently may be converted into the highly reactive hydroxyl radical (HO • ) (Valko et al, 2007), that may cause oxidative stressrelated damage (Carvalho et al, 2001, Duarte et al, 2004, Vaarmann et al, 2010, Costa et al, 2011.…”
Section: The Metabolites Of Catecholaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart is also a target for inflammation induced by drugs of abuse, due to catecholamine release induced by these drugs [169]. The hearts of rats treated with a methamphetamine binge administration regimen presented focal inflammatory infiltrates with abundant monocytes and occasional necrotic foci [170].…”
Section: Microglial Activation/inflammationmentioning
confidence: 99%